Utilization of Science and Technology in Community Empowerment in Kalipecabean Village, Sidoarjo Regency Through Integrated KKN Activities - Haq, Masyithoh Faarisatul; ‘Aini, Jafnah Kamilah; Ananda, Kharisma; Nurvita, Qur’ani; Ashari, Billa Laura; Oetarjo, Mas (Universitas Muhammadiyah Sidoarjo, 2025)
The Community Service Community Service Program (KKN) in Kalipecabean Village aims to support the development of village potential and improve community welfare through various empowerment activities. This activity includes local resource- based entrepreneurship training, increasing literacy and developing science and technology. By using field research methods. This research is included in qualitative descriptive research.